Prevalence and Antibiotic Resistance of in Respiratory Tract Samples: A 10-Year Epidemiological Snapshot - Márió Gajdács; Edit Urbán (SAGE Publishing, 2019)
Background: Since the 1980s, Stenotrophomonas maltophilia has emerged as an important pathogen associated with significant mortality in pneumonia and bacteremia of severely immunocompromised, hospitalized patients. The drug of choice in S maltophilia infections is sulfamethoxazole-trimethoprim (SMX/TMP); SMX/TMP resistance is a serious concern in clinical practice. The aim of this study was to assess the prevalence of S maltophilia in lower respiratory tract (LRTI) samples at a tertiary-care university hospital. Methods: This retrospective cohort study was carried out using microbiological data collected between January 2008 and December 2017. Routine antimicrobial susceptibility testing was performed for SMX/TMP and levofloxacin; in case of resistance, susceptibility testing for additional antibiotics (tigecycline, amikacin, and colistin) was also performed. Results: A total of 579 individual S maltophilia isolates were identified (2008-2012: n = 160, 2013-2017: n = 419; P = .0008). In all, 78.46% of patients were younger than 5 or older than 50 years of age and had recent trauma, surgery, or underlying conditions (malignancies, respiratory distress syndrome, congenital disorders, and cystic fibrosis). In 28.16% of samples, more than 1 pathogen was identified, and 5.35% of coisolated pathogens were multidrug resistant (MDR). In all, 12.1% of isolates were SMX/TMP-resistant (2008-2012: 6.12%, 2013-2017: 18.06%; P = .034), while 8.99% were resistant to levofloxacin (2008-2012: 7.86%, 2013-2017: 10.12%; P > .05). SMX/TMP resistance was detected more frequently in samples originating from inpatients (n = 2.50 ± 2.39 vs n = 11.50 ± 3.76; P = .0002). Conclusions: In all, 5.87% of isolates were extensively drug resistant (XDR), that is, in addition to SMX/TMP, they were resistant to levofloxacin, amikacin, colistin, and tigecycline. The results of our study correspond to the findings in the literature.